2019
DOI: 10.3390/molecules24152827
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and Bioavailability of the Major Metabolites of Crocus sativus L. Flower

Abstract: Crocus sativus L. has been cultivated throughout history to obtain its flowers, whose dried stigmas give rise to the spice known as saffron. Crocetin esters, picrocrocin, and safranal are the main metabolites of this spice, which possess a great bioactivity, although the mechanisms of action and its bioavailability are still to be solved. The rest of the flower is composed by style, tepals, and stamens that have other compounds, such as kaempferol and delphinidin, which have an important antioxidant capacity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 164 publications
(228 reference statements)
2
76
0
Order By: Relevance
“…Postharvest treatment is necessary to convert stigmas into saffron spice. Three molecules are the major determinants of the properties of saffron i.e., crocin, picrocrocin and safranal, responsible for the color, the flavor, and the aroma of saffron, respectively [ 85 ]. However, the concentrations of these saffron ingredients (and therefore the aroma, the color, and the flavor of saffron) depend on the drying and storage conditions, which are decisive for the quality of the spice [ 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Postharvest treatment is necessary to convert stigmas into saffron spice. Three molecules are the major determinants of the properties of saffron i.e., crocin, picrocrocin and safranal, responsible for the color, the flavor, and the aroma of saffron, respectively [ 85 ]. However, the concentrations of these saffron ingredients (and therefore the aroma, the color, and the flavor of saffron) depend on the drying and storage conditions, which are decisive for the quality of the spice [ 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the microwave-treated samples showed significant variance with the control, the values of which ranged from 20 in 800-40 to 48 in 616-83. Therefore, the saffron obtained by microwave dehydration contains less content of trans crocetin esters than those obtained from traditional "toasting", resulting in saffron with less bioactive capacity, as trans crocetin esters compounds are more bioactive than cis isomers [3,12,33].…”
Section: Content Of the Main Metabolites Of Microwave-dehydrated Saffronmentioning
confidence: 99%
“…However, emerging evidence has showed that saffron petals contain an array of bioactive polyphenols, including a series of flavonol glycosides and anthocyanin pigments. Several of these constituents were reported to possess multiple beneficial bioactivities [9], and on this evidence, a few extraction methodologies were developed, with the aim of producing polyphenol-containing extracts from saffron processing waste (SPW) [10][11][12][13].However, to the best of the authors' knowledge, the use of DES has never been reported for SPW extraction. The present investigation describes the development of a green extraction methodology for the effective recovery of SPW polyphenols, using a DES composed of L-lactic acid (HBD) and glycine (HBA).…”
mentioning
confidence: 99%